Nutritional and Sensory Quality and Heavy Metal Contents of Commercial Pork Products in West Bengal - Chowdhury, J.; Chakraborty, R.; Biswas, S.; Sahoo, S.; Das, S.K. (Journal of Meat Science, 2015)
A study was conducted to evaluate proximate composition, fatty acids and energy contents, heavy metal contents and consumer acceptance of ham, salami, sausages and nuggets produced at meat plant (bacon factory), Haringhata Farm, West Bengal. The mean of moisture (56.47 ± 0.150 to 64.70 ± 0.159), protein (16.23 ± 0.147 to 26.91 ± 0.145 ), total lipids (8.91 ± 0.129 to 18.87 ± 0.097) , mono unsaturated fatty acids (MUFA) (4.07 ± 0.028 to 8.87 ± 0.026), poly unsaturated fatty acids (PUFA) (0.95 ± 0.013 to 2.31 ± 0.027), saturated fatty acids (SFA) (3.04 ± 0.011to 6.83 ± 0.012), cholesterol (47.24 ± 0.128 to 62.11 ± 0.148) and energy content (191.60 ± 2.02 to 254.20 ± 2.01) were recorded. Heavy metal contents like copper (Cu) (0.74 ± 0.008 to 0.97 ± 0.009) and zinc (Zn) (5.59 ± 0.068 to 12.70 ± 0.132) were also recorded. Lead (Pb), arsenic (As) and tin (Sn) contents were at below detectable level (BDL). Proximate compositions were significantly (p0.05) in salami, sausages and nuggets though it differed significantly when compared with ham.
Keywords: Pork products; Proximate compositions; Fatty acids; Energy; Heavy metal; Sensory quality